Implementasi Pendekatan Ramah Anak dalam Pembelajaran Bahasa Kedua bagi Siswa Kebutuhan Khusus di RA Al-Khodijah Rejotangan - Alatas, Mochamad Arifin; Irma Rachmayanti; Sahrul Romadhon (Institut Agama Islam Negeri Madura, 2024)
This research is motivated by the second language learning (Arabic) for special needs students at RA Al-Khodijah Rejotangan. The study aims to describe this learning process, including planning, implementation, and evaluation. This research is qualitative descriptive in nature. Data collection techniques include interviews, observations, and documentation. The data sources for this research are the school principal, teachers, special needs students, and documents. The results of this study provide an overview of second language learning (Arabic) for special needs students at RA Al-Khodijah Rejotangan, including: (1) Lesson planning, which includes the curriculum, syllabus, and lesson plans like other schools. (2) Implementation of the learning process, which includes teaching materials such as Islamic religious books. The teaching methods include alphabet method, demonstration, religious studies, and lectures dominated by sign language. The learning media used are cards and (3) Evaluation of the learning process, which includes process and outcome evaluation indicating that special needs students can recognize Arabic letters but have difficulties in pronunciation.